Kualitas Layanan Fintech dan Literasi Investasi: Dampaknya terhadap Keberlanjutan Perbankan melalui Niat untuk Terus Menggunakan Aplikasi Seluler Bank Regional - Fazreen, Adinda; Firmialy, Sita Deliyana (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
The development of digital technology in the banking sector has driven significant transformation, including in mobile banking services. West Java Regional Banks, a regional development bank, has responded to this trend by launching the Mobileby Bank BJB application. This study examines how Fintech Service Quality and Sustainable Investment Literacy influence Bank Sustainable Performance and the mediating role of Continuance Intention in this relationship. The research is motivated by the gap between user expectations, the quality of services received, and the generally low level of user understanding regarding sustainability concepts, particularly in sustainable investment literacy. Using a quantitative approach and data analysis through questionnaire distribution, this study is expected to provide a clearer picture of the importance of improving digital service quality and sustainability literacy education in supporting the performance of digital banking. The findings are anticipated to offer strategic input for the development of Digi by Bank West Java Regional Bank in Indonesia and digital banking services in general, to be more competitive and aligned with user needs in the digital era.